2020
DOI: 10.1002/pts.2535
|View full text |Cite
|
Sign up to set email alerts
|

Changes of thermal properties and microstructure of nano‐ZnO/polylactic acid composite films during Zn migration

Abstract: In this study, polylactic acid (PLA) films with different nano-ZnO concentration (0, 1, 3, 5, 7, 9, and 15%wt) were obtained by casting method. Overall migration values and specific migration values were studied in different food simulants (10% [v/v] ethanol and isooctane). The results demonstrated that overall migration of the composite films and specific migration of Zn 2+ was higher in 10% (v/v) ethanol solution than in isooctane solution. The release of Zn 2+ was affected by the percentage of nano-ZnO in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…When ZnO is mixed with the polymer matrix, it acts as reinforcement. It boosts nanomaterials' thermal, barrier, and mechanical properties [124,125]. Table 5: Characteristics of toxic nanoparticles and their risk factors.…”
Section: Heating Effects On Nanomaterials In Food Packagingmentioning
confidence: 99%
See 2 more Smart Citations
“…When ZnO is mixed with the polymer matrix, it acts as reinforcement. It boosts nanomaterials' thermal, barrier, and mechanical properties [124,125]. Table 5: Characteristics of toxic nanoparticles and their risk factors.…”
Section: Heating Effects On Nanomaterials In Food Packagingmentioning
confidence: 99%
“…Then, the composite films were kept in the oven for a day at 40 °C. The PLA/ZnO composite films were prepared and named PLA-0, PLA-3, PLA-9, and PLA-15 [124,126].…”
Section: Size and Its Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2016) found that the migration of ZnO NPs from polypropylene food containers into food simulant solutions decreased as temperature decreased. Lu et al (2021) reported that migration of ZnO from polylactic acid films containing 1.0 -15.0% ZnO to food simulants increased as the concentration ZnO increased and that migration was higher in diluted 10% (v/v) ethanol solution compared to isooctane solution.…”
Section: Edx Analysismentioning
confidence: 99%
“…2 Many of these transition metals have been utilized as fungicides, algaecides, anti-fouling, and antibacterial agents in different forms such as salts, complexes, and encapsulated systems. [3][4][5][6][7][8] The biocidal efficacy of these metals varies with the type of transition metal, metallic or ionic state, and exposure to metal ion concentration since they can affect binding/adsorption of metal ions on the protein of microorganisms. 9,10 Besides, particle size, shape, aspect ratio, temperature, surface functionalization, and surrounding medium significantly impacts 9,11,12 accessibility to these metal ions.…”
Section: Introductionmentioning
confidence: 99%